Morphological Patterns Based on Space Syntax Theory in Small Type Housing in Malang City - Hayuningtyas, Widyotomo; Tutuko, Pindo; Aini, Nurul (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study examines the morphological pattern of small houses in Malang City using the space syntax method. The analysis was conducted to understand the impact of spatial structure on the social interactions and mobility of residents. Data was obtained through field observations and mapping, which were then analyzed to determine the relationship between the spatial configuration and daily activity patterns. The results show that the morphological pattern of housing designed according to the principles of space syntax can enhance social connectivity and accessibility between spaces, which has implications for the quality of life of residents. This finding is expected to serve as a reference for improved housing planning and development in urban areas. This study aims to analyze the morphological pattern of small houses based on the Space Syntax theory in Malang City. Primary data are collected through field surveys and direct measurements, while secondary data are obtained from relevant agencies. The results of the study show that there is a certain pattern in the structure of the housing space of small houses that have an impact on the connectivity and accessibility between the inside of the house and between houses in the surrounding environment, this shows that the morphological pattern of housing designed by considering the principle of space syntax can improve social connectivity and accessibility between spaces, which has implications for the quality of life of residents. This finding is expected to serve as a reference for improved housing planning and development in urban areas.